Transmission of exchange rate variation for brazilian export prices of iron ore: a comparative study of dollar and euro (Research, Society and Development, 2020)
The objective of this work consisted of the examination of the relation between exchange rate variations and the Brazilian export prices of iron ore, relation defined as the pass-through of the exchange rate, having as reference the period from January, 2000 to April, 2019. For this, we estimated two models: in dollar and in euro. The data were collected in the sites of Ministry of Development, Industry and Foreign Trade (MDIC), Institute of Applied Economics (IPEA) and in the MARKET INDEX. In this sense, we made use of timeseries instrumentals, especially the Error Correction Vector Model. The results found provided indications that the pass-through degree of exchange rate for the export prices of iron ore occurred in an incomplete form, with the coefficients for dollar and euro of, respectively, 0.84 and 0.77, representing that depreciations of exchange rate do not translate themselves into significant gains of competitiveness, since that they reduce partially the export prices.